Structural state scale-dependent physical characteristics and endurance of cermet composite for cutting metal; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Ovcharenko V. E. Vladimir Efimovich; Ivanov Yu. F. Yuriy Fedorovich; Mohovikov A. A.; Baohai Y. Yu; Zhao Y. Yanhui (2014, 2014)
Title screen